Using CT texture analysis to differentiate between nasopharyngeal carcinoma and age-matched adenoid controls. Issue 108 (November 2018) - Tsai, Amy; Buch, Karen; Fujita, Akifumi; Qureshi, Muhammad Mustafa; Kuno, Hirofumi; Chapman, Margaret N.; Li, Baojun; Oda, Masafumi; Truong, Minh Tam; Sakai, Osamu
Abstract: Objectives: To investigate the use of texture analysis to quantitatively distinguish nasopharyngeal carcinoma (NPC) from normal adenoid on CT. Methods: In this IRB-approved, retrospective study, nasopharyngeal tissues in 13 patients with NPC and 13 control patients were manually contoured, segmented, and imported to an in-house developed texture analysis program, which extracted 41 texture features. Basic descriptive statistics were performed to evaluate for differences in texture parameters between NPC and controls. Results: Statistically significant differences between NPC and controls were seen in 32 of 41 texture features. These significant differences were present in 11 of 12 histogram features, 4 of 5 gray-level co-occurrence matrix features, 7 of 11 gray-level run length features, 4 of 4 gray-level gradient matrix features, and 6 of 9 Laws features. Conclusion: Significant differences in many texture features were seen between NPC and normal adenoids. CT texture analysis may aid in differentiating NPC from normal adenoid tissue.